2014
DOI: 10.1371/journal.pone.0116063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of G6PD Genotypes and Phenotypes on the Northwestern Thailand-Myanmar Border

Abstract: Mutations in the glucose-6-phosphate dehydrogenase (G6PD) gene result in red blood cells with increased susceptibility to oxidative damage. Significant haemolysis can be caused by primaquine and other 8-aminoquinoline antimalarials used for the radical treatment of Plasmodium vivax malaria. The distribution and phenotypes of mutations causing G6PD deficiency in the male population of migrants and refugees in a malaria endemic region on the Thailand-Myanmar border were characterized. Blood samples for G6PD fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 29 publications
11
90
0
1
Order By: Relevance
“…AHA induced by 15 mg of daily PQ alone was well tolerated in healthy Cambodian Air Force men who had a mean baseline haemoglobin concentration of approximately 14 g/dL and which fell by a mean of 21 % on day (D)7, persisting to D15 [37]. Data in vivax-infected patients, with Hb concentrations ≥ 10 g/dL, showed that weekly-administered 0.75 mg base/kg of PQ resulted in a greater Hb level decline in G6PDd compared to G6PD normal patients.…”
Section: Introductionmentioning
confidence: 99%
“…AHA induced by 15 mg of daily PQ alone was well tolerated in healthy Cambodian Air Force men who had a mean baseline haemoglobin concentration of approximately 14 g/dL and which fell by a mean of 21 % on day (D)7, persisting to D15 [37]. Data in vivax-infected patients, with Hb concentrations ≥ 10 g/dL, showed that weekly-administered 0.75 mg base/kg of PQ resulted in a greater Hb level decline in G6PDd compared to G6PD normal patients.…”
Section: Introductionmentioning
confidence: 99%
“…G6PD-deficiency is very common among the refugee and migrant populations living on the Thai-Myanmar border [20]. This study will quantify the contribution of G6PD-deficiency to the incidence and severity of NH in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…G6PD Mahidol is the most common deficient variant (occurs in 88–96% of G6PD-deficient subjects) in Thai-Myanmar border area [2628]. This variant provides selective advantage against Plasmodium vivax but not against Plasmodium falciparum , which stipulates Plasmodium vivax has been the driving force for selective advantage conferred by Mahidol variant [29].…”
Section: Discussionmentioning
confidence: 99%